Effectiveness of Complementary and Alternative Medicine and Physical Therapies in Peripheral Arterial Disease with Intermittent Claudication: A Systematic Review - Alshammari, Mohammed Kanan; Hussain, Khansa Hamza; Alshammari, Maali Ramadan; Alshammari, Hanan Haif; Althagafi, Hadeel Saad; Bajunaid, Hanan Rashad; Alanzi, Bashayr Abdullah; Alshammari, Abdullah Ayed; Alshammari, Abdulaziz Khalaf; Aljasim, Mujtaba Abbas Jasim; Alanizi, Yazeed Saud; Al-Sulais, Wala’a Mohammed; et al. (Indian Journal of Pharmaceutical Education and Research, 2024)
Aim/Background Peripheral Arterial Disease (PAD) affects the lower limbs. Globally there is a growing disease burden among the patients suffering from cardio-vascular disease and metabolic disorders. The purpose of this review is to generate evidence on the efficacy of CAM therapies in PAD. Materials and Methods This systematic review was performed across the five electronic databases i.e. PubMed, Cochrane Central Register of Controlled Trials (CENTRAL), Ovid SP, ISI Web of Science, Elsevier Science Direct, and Wiley Online Library as per the PRISMA guidelines from inception till April 2022. Results After screening n=55,410 articles, n=77 articles were found to fulfill the eligibility criteria and were selected for this review. The nature of interventions investigated in the clinical trials were physical interventions including exercises of different forms, oral supplements, and other interventions such as chelation therapy, Tai Chi Chuan (TCC), Intermittent Mechanical Compression (IMC) device, connective tissue reflex massage, Remote Ischemic Preconditioning (RIC), Transcutaneous Electrical Nerve Stimulation (TENS) and heat therapy. Upon final assessment, it was revealed that physical activity had a positive effect on peripheral arterial disease patients’ quality of life. In addition,Ginkgo biloba and nitrate supplements were found effective for Intermittent Claudication (IC) and PAD patients. Conclusion This review suggests a positive impact of physical activity on peripheral arterial disease patients’ quality of life. Evidence also shows that Physical activity/ exercise-based intervention alone or in combination with the supplement is found to be effective among PAD patients and has shown significant results in intermittent claudication.
Keywords: Peripheral arterial disease; Complementary medicine; Alternative medicine; Review; Intermittent claudication